Applications of FRP in Civil Structures of India - Mukherjee, Abhijit (tbc, 2013)
The Research on Civil Engineering applications of FRP in India has a history of nearly twenty years. Applications of the technology in infrastructure were initially a trickle. The first major project was after the earthquake of 2001 in Gujarat. In the last decade the technology has gained popularity and created a niche for itself. However, there are significant challenges to its progress.